COMMUNITY-BASED FOREST GOVERNANCE MODELS IN SOUTHEAST ASIA: BETWEEN LOCAL WISDOM AND STATE POLICY - Tan, Ethan; Lee, Ava; Wong, Lucas (Journal of Selvicoltura Asean, 2026)
Southeast Asia’s forests are critical to both global biodiversity and local livelihoods. Yet, these ecosystems are under significant threat from deforestation, climate change, and unsustainable resource extraction. The governance of forest resources in the region remains a complex issue, as it involves the interaction between local communities’ traditional knowledge and practices, and state policies aimed at forest conservation and management. Understanding the dynamics of community-based forest governance models, which integrate local wisdom with state regulations, is crucial for achieving sustainable forest management. This study aims to examine the role of community-based forest governance models in Southeast Asia, with a particular focus on how local wisdom and state policy intersect. The research seeks to explore the challenges and opportunities in aligning indigenous governance practices with formal state policies for effective forest management. A qualitative approach was employed, utilizing case studies from various Southeast Asian countries, including Indonesia, Thailand, and the Philippines. Data were gathered through interviews with community leaders, government officials, and forest managers, as well as field observations. The findings highlight that while local communities possess valuable ecological knowledge, there are often conflicts with state policies that prioritize top-down forest management. However, successful models exist where collaboration between communities and state actors leads to more sustainable outcomes. The study underscores the importance of integrating local wisdom with state policies to create more effective and inclusive forest governance frameworks.